Synthesis and biodegradability of polyaspartic acid: a critical review - Thombre, SM; Sarwade, BD (Journal of Macromolecular Science-Pure and Applied Chemistry, 2005)
Poly(aspartic acid) (PAA) being biodegradable is suitable for various industrial medical and agricultural applications to replace many non-biodegradable polymers in use. Poly(aspartic acid) can be synthesized by different methods with and without catalyst in different forms such as polysuccinimide, either hydrolyzed to acid or salt. The polymer of (aspartic acid) is present in different forms such as alpha, beta and L, D isomers. The conformational analysis of poly(aspartic acid) was done by various analytical methods. Different combinations of these two isomer present in different percentage can be detected by various methods such as Hoffman degradation, IR, and NMR spectroscopic analysis. From the standard test for biodegrad ability, it was shown that the polymer is fully biodegradable. In this review, synthesis and characterization of homo and copolymer derivatives of PAA, along with the application and biodegradability in comparison with the other polymer in use, is discussed briefly.
Keywords: Biodegradation; poly(aspartic acid); Polycondensation; polysuccinimide; synthesis; thermal

Chemical, thermal and pH-induced equilibrium unfolding studies of fusarium solani lectin - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The effect of urea, guanidine thiocyanate, temperature and pH was studied on the conformational stability of Fusarium solani lectin. Equilibrium unfolding with chemical denaturants showed that the lectin was least stable at pH 12 and maximally stable at pH 8.0 near its pI ( 8.7). Guanidine thiocyanate ( the concentration of denaturant at which the protein is half folded, D-1/2 = 0.49 M at pH 12) was found to be an eight times stronger denaturant than urea (D-1/2 = 3.88 M at pH 12). The unfolding curves obtained with fluorescence and CD measurements showed good agreement indicating a monophasic nature of unfolding and excluded the possibility of formation of any stable intermediate. The effect of pH on the lectin was found to be unusual as at acidic pH, the lectin showed a flexible tertiary structure with pronounced secondary structure, and retained its hemagglutinating activity. On the other hand, the lectin did not show any loss of conformation or activity upto 70 degrees C for 15 min. Moreover, thermal denaturation did not result in the aggregation or precipitation of the protein even at high temperatures. Thermal denaturation was also carried out in the presence of a low concentration of guanidine thiocyanate. Change in the enthalpy of transition (Delta H-m) varied linearly with transition temperature (T-m), which indicated that the heat capacity (Delta C-p =3.95 kJ (.) mol(-1) (.) K-1) of the lectin remained constant during the unfolding.
Keywords: Denaturation; Fusarium solani; guanidine; Lectin; thermal; Unfolding

Examining the compatibility of energetic plasticizer DNDA-5 with energetic binders - Vijayalakshmi, R.; Agawane, N. T.; Talawar, M. B.; Khan, Md Abdul Shafeeuulla (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2020)
The requirement of developing energetic binders with suitable energetic plasticizers is to enhance the mechanical properties and to reduce glass transition temperature of propellant and explosive formulations. Compatibility of energetic plasticizer 2,4-dinitro-2,4-diazapentane (DNDA-5) with four different energetic binders viz. poly glycidyl nitrate (PGN), poly(3-nitratomethyl-3-methyloxetane) (PLN), glycidyl azide polymer (GAP) and tetra functional glycidyl azide polymer (t-GAP) was studied by using differential scanning calorimeter (DSC) and density functional theory (DFT) methods. Results obtained for the pure binder was compared with the results obtained for binder/plasticizer blend in the parameters of decomposition temperature and the format of the peak which indicated the compatibility or incompatibility of DNDA-5 with the studied binders. Glass transition temperatures of all these blends were determined by low temperature DSC and showed desirable lowering of glass transition temperature with single peak in the case of PLN. The proposed energetic plasticizer DNDA-5 has displayed its compatibility with three binders PGN, PLN and GAP employing thermal techniques. DNDA-5 has been found as incompatible when it is mixed with t-GAP. The predicted relative trend of interaction energies between plasticizer and binder has provided concurrence to results drawn from thermal studies.
Keywords: Computational study; DNDA-5; Glass transition temperature; plasticizing effect; thermal